Paratuberculosis bovina: ¿conocemos la situación real de la enfermedad en la ganadería colombiana? - Zapata R., Margarita M.; Rodas G., Juan David; Maldonado Estrada, Juan Guillermo (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Mycobacterium avium subspecies paratuberculosis (Map) is the etiologic agent of a severe granulomatous gastroenteritis in ruminants, known as bovine paratuberculosis or Johne's disease and characterized by persistent diarrhea and progressive emaciation that finally cause death. Calves under 6 months of age are the most susceptible to this bacterial infection by transplacental route, milk consumption or grassland contaminated feeding and although, they do not show clinical signs until they are 2 to 5 years old (incubation period), they commonly spread Map through their feces. A remarkable difficulty concerning Johne´s disease is its lack of appropriate treatment; therefore any control scheme must be focused in identification of infected animals by reliable diagnostic tests before the appearance of clinical manifestations, in order to avoid dissemination of the infection to animals of the same or different herd, particularly when marketing possible asymptomatic animals. The infection has a worldwide distribution and it is responsible of important economic losses in cattle industry. Bear to us, the disease has been reported in dairy herds of the municipality of San Pedro de los Milagros (Antioquia), but it is thought that there are many other infected regions, which makes more prominent the need of efficient methods for Map detection for rapid diagnosis and efficient control of the dissemination of the infection. In this review, we highlight some important features of bovine paratuberculosis and provide some insight regarding probable research perspectives of this disease.